Online tools to support teaching and training activities in chemical engineering: enzymatic proteolysis - Villaró-Cos, Silvia; Lafarga, Tomas (Frontiers in Education, 2023)
The practical teaching or training of enzymatic proteolysis can prove challenging because of the lengthy duration of the process, the complexity of identifying short amino acid sequences, the high cost of the enzymes, and the need to use very specific equipment. There are several freely-available online tools that, despite being employed by scientists to help identify bioactive peptides, are not commonly used for teaching and training activities. This work summarises the most common protein and peptide databases along with other tools that allow one to simulate enzymatic hydrolysis of a given protein and to study the structure, physicochemical properties, bioactivity, toxicity, allergenicity, and even the bitterness of the resulting peptides. Overall, in silico tools can be used during the teaching and training of chemical engineers as innovative alternatives to conventional laboratory work and theoretical classes.